2021
DOI: 10.3390/antibiotics10060660
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different β-Lactam Antibiotics on Indirect Tomato (Solanum lycopersicum L.) Shoot Organogenesis and Agrobacterium tumefaciens Growth Inhibition In Vitro

Abstract: A β-lactams that act by inhibiting the bacterial cell wall biosynthesis are one of the most common classes of antibiotics applied to suppress the growth of latent bacterial infection associated with the plant tissue culture, as well as in the Agrobacterium-mediated transformation techniques. Plant sensitivity to antibiotics usually is species-, genotype-, or even tissue-specific and mainly depends on concentrations, growth conditions, and culture system. In the presented article, we estimated a comparative eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…These authors suggested that auxin-like degradation products of timentin could be playing a role in this increased regeneration. ( Varlamova et al., 2021 ) showed that timentin and Amoxicillin enhanced shoot organogenesis in tomato is concentration and genotype dependent. They suggested that the positive effects of these antibiotics on shoot organogenesis is probably due to the presence of clavulanic acid or its degradation products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors suggested that auxin-like degradation products of timentin could be playing a role in this increased regeneration. ( Varlamova et al., 2021 ) showed that timentin and Amoxicillin enhanced shoot organogenesis in tomato is concentration and genotype dependent. They suggested that the positive effects of these antibiotics on shoot organogenesis is probably due to the presence of clavulanic acid or its degradation products.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a positive effect of β-lactam ring-containing antibiotics such as timentin, carbenicillin, and penicillin G on shoot regeneration in species such as tomato, tobacco, and London plane tree. This effect was found to be dependent on the antibiotic concentration and plant genotype ( Nauerby et al., 1997 ; Ling et al., 1998 ; Costa et al., 2000 ; Li et al., 2007 ; Varlamova et al., 2021 ). In contrast, some studies have also reported no significant effect of these antibiotics on shoot regeneration in species such as tobacco and Siberian elm ( Cheng et al., 1998 ).…”
Section: Introductionmentioning
confidence: 95%
“…Like beta-lactam antibiotics, cefotaxime, carbenicillin, penicillin G, and some other antibiotics were found effective during somatic embryogenesis, axillary bud formation, and shoot induction in dainthus and Solanum viarum ( Nakano and Mii, 1993 ; Mahadev et al, 2014 ). Amoxiclav was found to increase morphogenesis and shoot regeneration in maize, carrot, and tomato, respectively ( Danilova and Dolgikh, 2005 ; Grzebelus and Skop, 2014 ; Varlamova et al, 2021 ). However, if we utilized this during co-cultivation, its antibacterial activities against gram-negative bacteria might impede bacterial development.…”
Section: Discussionmentioning
confidence: 99%
“…Timentin is a formulation that provides stability to the β-lactam ring in the broad-spectrum semi-synthetic β-lactam antibiotic ticarcillin by combining it with clavulanic acid, a β-Lactamase competitive inhibitor [24,25]. Timentin has been demonstrated to have a favorable impact on shoot regeneration in several plant species, including London plane trees, tomato, and tobacco, along with a few other β-lactam ring-containing antibiotics like penicillin G and carbenicillin [23,[26][27][28]. Conversely, other research has also shown that these antibiotics have no appreciable impact on the regeneration of shoots in species like tobacco and Siberian elm [29,30].…”
Section: Introductionmentioning
confidence: 99%